The study of parasites infestation on wild giant freshwater prawn, Macrobrachium rosenbergii in Peninsular Malaysia - Choong, Foong Choong (Institut Akuakultur Tropika, 2012)
Wild giant freshwater prawn Macrobrachium rosenbergii (de Man, 1879)collected from Sungai Timun (Negeri Sembilan) and Sungai Rubana (Perak) of Peninsular Malaysia, during the period October 2008 to Feb 2010, was subjected to the study of morphology and prevalence of various parasites due to rainfall changes.